2021
DOI: 10.1352/1944-7558-126.2.114
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Single-Case Research on Applied Behavior Analytic Interventions for People With Down Syndrome

Abstract: This systematic review evaluates single-case research design studies investigating applied behavior analytic (ABA) interventions for people with Down syndrome (DS). One hundred twenty-five studies examining the efficacy of ABA interventions on increasing skills and/or decreasing challenging behaviors met inclusion criteria. The What Works Clearinghouse standards and Risk of Bias in N-of-1 Trials scale were used to analyze methodological characteristics, and Tau-U effect sizes were calculated. Results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 133 publications
1
2
0
2
Order By: Relevance
“…The discussion is as follows: Firstly, after the intervention of physical activity, the core symptoms of ASD were increased by a moderate effect size (ES = 0.702). This is consistent with the results that physical activity can improve social communication deficits or stereotyped and repetitive behaviors in people with neurological, emotional and behavioral disorders such as ADHD (Hoza et al, 2016), and Down syndrome (Neil et al, 2021). Previous studies have shown that white matter damage, myelin sheath dysplasia, and abnormal neural connections are related to the pathological mechanism of ASD (Solders et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The discussion is as follows: Firstly, after the intervention of physical activity, the core symptoms of ASD were increased by a moderate effect size (ES = 0.702). This is consistent with the results that physical activity can improve social communication deficits or stereotyped and repetitive behaviors in people with neurological, emotional and behavioral disorders such as ADHD (Hoza et al, 2016), and Down syndrome (Neil et al, 2021). Previous studies have shown that white matter damage, myelin sheath dysplasia, and abnormal neural connections are related to the pathological mechanism of ASD (Solders et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Also, we used Tau‐ U to identify the effectiveness of each study on increasing on‐task behaviors. Many recent reviews on behavior management used Tau‐ U method (Chaffee et al, 2017; Muharib et al, 2021; Neil et al, 2021). While PND (percentage of non‐overlapping data) has been used extensively in many single case research studies despite its limitations, Tau‐ U has gained attention from researchers and has been widely used in educational research.…”
Section: Discussionmentioning
confidence: 99%
“…A Análise do Comportamento Aplicada, muito conhecida pelo seu uso em pessoas com autismo, também tem sido estudada, a partir do delineamento de caso único, para pessoas com síndrome de down (e.g. Neil et al, 2021). Na área da neurorreabilitação houve um aumento exponencial de estudos com esse delineamento nos últimos 50 anos (Vlaeyen et al, 2020).…”
Section: Delineamentos De Caso úNicounclassified